2003
DOI: 10.1159/000070187
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione S-Transferase Polymorphisms: Susceptibility to Migraine without Aura

Abstract: Migraine is considered to be a polygenic multifactorial disease with various environmental and genetic etiologies. We investigated glutathione S-transferase (GST) P1 Ile105Val, T1 and M1 polymorphisms in 174 Japanese headache sufferers and 372 Japanese controls. The headache group consisted of 38 cases of migraine with aura, 95 migraine without aura (MWOA) and 41 tension-type headache sufferers. The M1 homozygous deletion genotype was significantly higher in MWOA (64%) compared with controls (46%; p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…However, subsequent reports have not confirmed an association, as has often been the case with this method of analysis (Lea et al 2000;Maude et al 2001). Other genes with suggested polymorphisms associated with migraine include glutathione-S-transferase/GST (MO; Kusumi et al 2003), dopamine receptor type 4/DRD4 (MO; Mochi et al 2003), TNF-β /lymphotoxin alpha (MO; Trabace et al 2002), interleukin 1A/IL-1A (Rainero et al 2002b), serotonin transporter (Yilmaz et al 2001), the C677T methyl-tetrahydrofolate reductase allele/MTHFR (Kowa et al 2000), the dopamine beta hydroxylase gene/DBH (Lea et al 2000), angiotensin-converting enzyme-DD allele/ACE-DD (Paterna et al 2000), ABO to alpha-1-antitrypsin among group components (Chr4; Pardo et al 1995), and esterase-D (Chr13; Pardo et al 1995).…”
Section: Genome Scans For Familial Migrainementioning
confidence: 98%
“…However, subsequent reports have not confirmed an association, as has often been the case with this method of analysis (Lea et al 2000;Maude et al 2001). Other genes with suggested polymorphisms associated with migraine include glutathione-S-transferase/GST (MO; Kusumi et al 2003), dopamine receptor type 4/DRD4 (MO; Mochi et al 2003), TNF-β /lymphotoxin alpha (MO; Trabace et al 2002), interleukin 1A/IL-1A (Rainero et al 2002b), serotonin transporter (Yilmaz et al 2001), the C677T methyl-tetrahydrofolate reductase allele/MTHFR (Kowa et al 2000), the dopamine beta hydroxylase gene/DBH (Lea et al 2000), angiotensin-converting enzyme-DD allele/ACE-DD (Paterna et al 2000), ABO to alpha-1-antitrypsin among group components (Chr4; Pardo et al 1995), and esterase-D (Chr13; Pardo et al 1995).…”
Section: Genome Scans For Familial Migrainementioning
confidence: 98%
“…Migraine Type/Features Action in Relation to Migraine Dopamine type 2 (D2) receptor 23 Migraine with and without aura 23,91 • Vasoconstriction • Reduces trigeminal nerve activation • Inhibits release of vasoactive neuropeptide • Interrupts pain transmission centrally Glutathione S-transferase 92 Migraine without aura 92 • Increases susceptibility to environmental xenobioticinduced migraine attacks in GSTM1 genotype Dopamine type 4 (D4) receptor 93 Migraine without aura 93 • A potential genetic association exists between dopamine D4 receptor gene and migraine without aura Tumor necrosis factor-a 94 Migraine without aura 95 • Proinflammatory cytokine Methyltetrahydrofolate reductase (MTHFR) C677T allele 96 Migraine with aura 96 • MTHFR C677T polymorphism may increase homocysteine levels associated with migraine with aura Dopamine b-hydroxylase gene 97 Migraine with aura 97 • An intracellular enzyme catalyzing the conversion of dopamine to noradrenaline; imbalance may increase susceptibility to migraine Angiotensin-converting enzyme allele 98 Migraine with and without aura 90,99,100 • Involved in vasoconstriction and vascular remodeling…”
Section: Gene Productmentioning
confidence: 99%
“…Conflicting results of this nature may arise due to differing allele frequencies amongst distinct ethnicities. In addition to the positive findings of GSTM1 in the Japanese cohort, Kusumi et al [86] concluded no genetic involvement of GSTP1 or GSTT1 in migraine susceptibility.…”
Section: Glutathione S-transferase Genesmentioning
confidence: 97%
“…The null genotype of the GSTM1 gene, resulting in no expression of the GSTM1 protein, was found not to be involved in a Swedish migraine cohort. However, an independent Japanese study reported an increased frequency of the GSTM1 null genotype in MO only affected individuals [86] . Conflicting results of this nature may arise due to differing allele frequencies amongst distinct ethnicities.…”
Section: Glutathione S-transferase Genesmentioning
confidence: 97%